Management of nausea and vomiting symptoms induced by chemotherapy: an integrative review (Research, Society and Development, 2020)
Chemotherapy is one of the therapies available to cancer patients undergoing neoadjuvant, adjuvant or palliative treatment. Among the most prevalent symptoms, there is nausea and vomiting induced by chemotherapy, being considered side effects, which cause fragility and suffering to some patients. The study aims to know the measures found for the control of nausea and vomiting induced by chemotherapy in adult cancer patients. It is an integrative review, of a qualitative nature, whose analysis will be of an exploratory approach. The study consisted of eight articles selected from the Pubmed and Scielo databases between 2015 and 2020. It was noted that despite advances in pharmacological and non-pharmacological therapies and the provision of standard clinical guidelines for the effective management of nausea and vomiting induced by chemotherapy, patients continue to experience these symptoms in most cases. The need to intensify research on non-pharmacological strategies to optimize the management of this problem was evidenced, since controlling the side effects of a chemotherapy treatment provides excellence in care and quality of life for patients.